Analysis of Traffic Accidents in Slovenia as a Basis for the Deployment of Automated Measurement Systems - Glavan, Tim; Živković, Sašo; Meško, Maja (Prometna varnost v lokalnem okolju: problemsko-učno sodelovanje z Intermatic d.o.o., 2026)
This chapter addresses road safety in Slovenia and the role of automated measurement systems in improving road safety indicators. The purpose of the work is to determine which factors of traffic accidents are most strongly associated with serious consequences, how risk is distributed across space and time, and which groups of road users are most at risk. A quantitative secondary analysis of the national police traffic accident database for 2025 was used, comprising 17,186 accidents and 30,404 participants. The results indicate that inappropriate speed is by far the strongest predictor of severe consequences, that accidents with the most serious outcomes are concentrated in smaller administrative units and outside urban areas, and that pedestrians, cyclists, and motorcyclists are disproportionately exposed to risk. The quantitative findings were complemented by an interview with a field expert, which further illuminated the interpretation of the results. Based on the results, a priority ranking of road safety critical locations was developed, together with a strategic framework for systems integrating speed enforcement, traffic signal monitoring, and the protection of vulnerable road users. Recommendations for the company include expanding to smaller but higher-risk municipalities and developing systems for detecting vulnerable road users.